The general theory of employment, interest and money - Keynes, John Maynard, 1883-1946. (Macmillan for the Royal Economic Society, 1973)
Introduction. Definitions and ideas. The propensity to consume. The inducement to invest. Money-wages and prices. Short notes suggested by the general theory.